(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article presents a theoretical analysis of the content of the concept of the culture of movement, which in modern science is presented as a multifaceted phenomenon. As a 58 phenomenon of general culture, the culture of movement is considered as a process of using the values of physical culture in various types of human motor activity. The culture of movement, as a component of physical culture, is presented as a reflection of all its aspects. The formation of a culture of movement should be considered both as a task and as a result of the process of physical education. There are three levels of movement culture formation: basic, optimal and high. The analysis of scientific and methodological literature on the problem under study made it possible to single out a number of issues that remain insufficiently studied. Further research will be aimed at determining the criteria for assessing the level of formation of the culture of movement, the development of ways of its directed development in the process of physical education.